At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Let's solve each part of the question step-by-step.
### Part (1)
We want to express \( f^n(x) \) in terms of \( a, b, x, n \).
Given the function \( f(x) = ax + b \), we can construct the first few iterations of \( f \):
- For \( n = 1 \), \( f^1(x) = f(x) = ax + b \).
- For \( n = 2 \), \( f^2(x) = f(f(x)) = f(ax + b) = a(ax + b) + b = a^2x + ab + b \).
- For \( n = 3 \), \( f^3(x) = f(f^2(x)) = f(a^2x + ab + b) = a(a^2x + ab + b) + b = a^3x + a^2b + ab + b \).
To find a general form, we notice a pattern. Each iteration adds another factor of \( a \) to the term involving \( x \) and accumulates the constants \( b \) influenced by the power of \( a \):
[tex]\[ f^n(x) = a^n x + b(1 + a + a^2 + \cdots + a^{n-1}) \][/tex]
The sum \( 1 + a + a^2 + \cdots + a^{n-1} \) is a geometric series with sum given by \(\frac{1-a^n}{1-a}\) (since \( |a| < 1 \)):
[tex]\[ f^n(x) = a^n x + b \cdot \frac{1-a^n}{1-a} \][/tex]
So,
[tex]\[ \boxed{f^n(x) = a^n x + \frac{b(1-a^n)}{1-a}} \][/tex]
### Part (2)
We want to express \(\frac{f^n(x) - f^{n-1}(x)}{a^n}\) in terms of \( a, b, x, n \).
From part (1), we have:
[tex]\[ f^n(x) = a^n x + \frac{b(1-a^n)}{1-a} \][/tex]
[tex]\[ f^{n-1}(x) = a^{n-1} x + \frac{b(1-a^{n-1})}{1-a} \][/tex]
The difference is:
[tex]\[ f^n(x) - f^{n-1}(x) = \left( a^n x + \frac{b(1-a^n)}{1-a} \right) - \left( a^{n-1} x + \frac{b(1-a^{n-1})}{1-a} \right) \][/tex]
[tex]\[ = a^n x - a^{n-1} x + b \left( \frac{1-a^n}{1-a} - \frac{1-a^{n-1}}{1-a} \right) \][/tex]
[tex]\[ = a^{n-1}(ax - x) + b \left( \frac{a^{n-1}(a-1)}{1-a} \right) \][/tex]
[tex]\[ = a^{n-1}x(a - 1) + b \left( -a^{n-1} \right) \][/tex]
[tex]\[ = a^{n-1}\cdot (a-1)x - a^{n-1}b \][/tex]
Dividing by \( a^n \):
[tex]\[ \frac{f^n(x) - f^{n-1}(x)}{a^n} = \frac{a^{n-1}(ax - x) - b a^{n-1}}{a^n} \][/tex]
[tex]\[ = \frac{a^{n-1}(a - 1)x - b a^{n-1}}{a^n} \][/tex]
[tex]\[ = \frac{(a - 1)x - b}{a} \][/tex]
So,
[tex]\[ \boxed{\frac{f^n(x) - f^{n-1}(x)}{a^n} = \frac{(a - 1)x - b}{a}} \][/tex]
### Part (3)
Consider the curve \( y = \frac{f^n(x) - f^{n-1}(x)}{a^n} \) and the line \( y = ax + b \). We need to find their intersection point \( Q(x_n, y_n) \).
From part (2), the curve is \( y = \frac{(a-1)x - b}{a} \).
Setting these equal:
[tex]\[ ax + b = \frac{(a-1)x - b}{a} \][/tex]
Multiply both sides by \( a \):
[tex]\[ a^2x + ab = (a-1)x - b \][/tex]
Collecting like terms:
[tex]\[ a^2 x - (a-1)x = - b - ab \][/tex]
[tex]\[ (a^2 - a + 1)x = - b(1 + a) \][/tex]
[tex]\[ x_n = \frac{- b(1 + a)}{a^2 - a + 1} \][/tex]
Substitute \( x_n \) into \( y = ax + b \):
[tex]\[ y_n = a\left( \frac{- b(1+a)}{a^2 - a + 1} \right) + b \][/tex]
Simplifying \( y_n \):
[tex]\[ y_n = \frac{- ab(1 + a)}{a^2 - a + 1} + b \][/tex]
[tex]\[ = \frac{- ab(1 + a) + b(a^2 - a + 1)}{a^2 - a + 1} \][/tex]
[tex]\[ = \frac{b(a^2 - ab - ab - a + b)}{a^2 - a + 1} \][/tex]
[tex]\[ y_n = \frac{b(a^2 - 2ab - a + 1)}{a^2 - a + 1} \][/tex]
Thus,
[tex]\[ \boxed{x_n = \frac{- b(1 + a)}{a^2 - a + 1}} \][/tex]
[tex]\[ \boxed{y_n = \frac{b(a^2 - 2ab - a + 1)}{a^2 - a + 1}} \][/tex]
### Part (4)
Calculate the limit \(\lim_{n \rightarrow \infty} f^n(x)\).
From part (1), \( f^n(x) = a^n x + \frac{b(1-a^n)}{1-a} \).
As \( n \rightarrow \infty \), since \( -1 < a < 1 \), \( a^n \rightarrow 0 \):
[tex]\[ \lim_{n \to \infty} f^n(x) = 0 \cdot x + \frac{b(1-0)}{1-a} \][/tex]
[tex]\[ = \frac{b}{1-a} \][/tex]
Thus,
[tex]\[ \boxed{\lim_{n \rightarrow \infty} f^n(x) = \frac{b}{1-a}} \][/tex]
### Part (1)
We want to express \( f^n(x) \) in terms of \( a, b, x, n \).
Given the function \( f(x) = ax + b \), we can construct the first few iterations of \( f \):
- For \( n = 1 \), \( f^1(x) = f(x) = ax + b \).
- For \( n = 2 \), \( f^2(x) = f(f(x)) = f(ax + b) = a(ax + b) + b = a^2x + ab + b \).
- For \( n = 3 \), \( f^3(x) = f(f^2(x)) = f(a^2x + ab + b) = a(a^2x + ab + b) + b = a^3x + a^2b + ab + b \).
To find a general form, we notice a pattern. Each iteration adds another factor of \( a \) to the term involving \( x \) and accumulates the constants \( b \) influenced by the power of \( a \):
[tex]\[ f^n(x) = a^n x + b(1 + a + a^2 + \cdots + a^{n-1}) \][/tex]
The sum \( 1 + a + a^2 + \cdots + a^{n-1} \) is a geometric series with sum given by \(\frac{1-a^n}{1-a}\) (since \( |a| < 1 \)):
[tex]\[ f^n(x) = a^n x + b \cdot \frac{1-a^n}{1-a} \][/tex]
So,
[tex]\[ \boxed{f^n(x) = a^n x + \frac{b(1-a^n)}{1-a}} \][/tex]
### Part (2)
We want to express \(\frac{f^n(x) - f^{n-1}(x)}{a^n}\) in terms of \( a, b, x, n \).
From part (1), we have:
[tex]\[ f^n(x) = a^n x + \frac{b(1-a^n)}{1-a} \][/tex]
[tex]\[ f^{n-1}(x) = a^{n-1} x + \frac{b(1-a^{n-1})}{1-a} \][/tex]
The difference is:
[tex]\[ f^n(x) - f^{n-1}(x) = \left( a^n x + \frac{b(1-a^n)}{1-a} \right) - \left( a^{n-1} x + \frac{b(1-a^{n-1})}{1-a} \right) \][/tex]
[tex]\[ = a^n x - a^{n-1} x + b \left( \frac{1-a^n}{1-a} - \frac{1-a^{n-1}}{1-a} \right) \][/tex]
[tex]\[ = a^{n-1}(ax - x) + b \left( \frac{a^{n-1}(a-1)}{1-a} \right) \][/tex]
[tex]\[ = a^{n-1}x(a - 1) + b \left( -a^{n-1} \right) \][/tex]
[tex]\[ = a^{n-1}\cdot (a-1)x - a^{n-1}b \][/tex]
Dividing by \( a^n \):
[tex]\[ \frac{f^n(x) - f^{n-1}(x)}{a^n} = \frac{a^{n-1}(ax - x) - b a^{n-1}}{a^n} \][/tex]
[tex]\[ = \frac{a^{n-1}(a - 1)x - b a^{n-1}}{a^n} \][/tex]
[tex]\[ = \frac{(a - 1)x - b}{a} \][/tex]
So,
[tex]\[ \boxed{\frac{f^n(x) - f^{n-1}(x)}{a^n} = \frac{(a - 1)x - b}{a}} \][/tex]
### Part (3)
Consider the curve \( y = \frac{f^n(x) - f^{n-1}(x)}{a^n} \) and the line \( y = ax + b \). We need to find their intersection point \( Q(x_n, y_n) \).
From part (2), the curve is \( y = \frac{(a-1)x - b}{a} \).
Setting these equal:
[tex]\[ ax + b = \frac{(a-1)x - b}{a} \][/tex]
Multiply both sides by \( a \):
[tex]\[ a^2x + ab = (a-1)x - b \][/tex]
Collecting like terms:
[tex]\[ a^2 x - (a-1)x = - b - ab \][/tex]
[tex]\[ (a^2 - a + 1)x = - b(1 + a) \][/tex]
[tex]\[ x_n = \frac{- b(1 + a)}{a^2 - a + 1} \][/tex]
Substitute \( x_n \) into \( y = ax + b \):
[tex]\[ y_n = a\left( \frac{- b(1+a)}{a^2 - a + 1} \right) + b \][/tex]
Simplifying \( y_n \):
[tex]\[ y_n = \frac{- ab(1 + a)}{a^2 - a + 1} + b \][/tex]
[tex]\[ = \frac{- ab(1 + a) + b(a^2 - a + 1)}{a^2 - a + 1} \][/tex]
[tex]\[ = \frac{b(a^2 - ab - ab - a + b)}{a^2 - a + 1} \][/tex]
[tex]\[ y_n = \frac{b(a^2 - 2ab - a + 1)}{a^2 - a + 1} \][/tex]
Thus,
[tex]\[ \boxed{x_n = \frac{- b(1 + a)}{a^2 - a + 1}} \][/tex]
[tex]\[ \boxed{y_n = \frac{b(a^2 - 2ab - a + 1)}{a^2 - a + 1}} \][/tex]
### Part (4)
Calculate the limit \(\lim_{n \rightarrow \infty} f^n(x)\).
From part (1), \( f^n(x) = a^n x + \frac{b(1-a^n)}{1-a} \).
As \( n \rightarrow \infty \), since \( -1 < a < 1 \), \( a^n \rightarrow 0 \):
[tex]\[ \lim_{n \to \infty} f^n(x) = 0 \cdot x + \frac{b(1-0)}{1-a} \][/tex]
[tex]\[ = \frac{b}{1-a} \][/tex]
Thus,
[tex]\[ \boxed{\lim_{n \rightarrow \infty} f^n(x) = \frac{b}{1-a}} \][/tex]
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.